Analisis Implementasi Strategi Cross Selling Oleh Frontliner Pada PT Pegadaian CP Basen Yogyakarta - Melinda Putri Aprilia Simatupang; Indah Respati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The rise in energy prices and reference interest rates, including in Indonesia, has caused inflation to spike. PT Pegadaian offers a solution for individuals facing financial difficulties during inflation by providing loans with valuable items as collateral. To adapt to the inflationary situation, PT Pegadaian employs cross-selling strategies, primarily through face-to-face interactions and social media. This study, conducted at PT Pegadaian CP Basen Yogyakarta, aims to understand the implementation of cross-selling by frontliners and identify challenges. This research falls under a field study with a qualitative descriptive method, utilizing both primary and secondary data sources. Data collection techniques include literature research and field research. The results of the analysis reveal that the implementation of the cross-selling strategy remains unchanged, similar to the period before the inflation increase. This involves offering Pegadaian products through face-to-face interactions and social media. Challenges faced by Frontliner Pegadaian CP Basen Yogyakarta in implementing the cross-selling strategy include limited marketing time, customers already using similar products from other institutions, and a lack of customer knowledge regarding the variety of products offered by Pegadaian